Studi Analisis Kualitas Air Lau Borus (Outlet Danau Lau Kawar), Pasca Erupsi Gunung Sinabung Di Kecamatan Naman Teran, Kabupaten Karo, Provinsi Sumatera Utara - Said Muzambiq; Meutia Nurfahasdi; Sarah Fatalosa Manalu Tavi Ni Amida (Widya Teknik, 2022)
Lau borus is an outlet located on Lau Kawar Lake. The location of lau borus is located at the foot of mount sinabung where this mountain has experienced quite high eruptive activity for several years. Determination of the status of water quality in these waters using the Pollution Index Method following the Regulation of the Minister of the Environment number 115 of 2003 and the Regulation of the Minister of Health Number 32 of 2017. The parameters that will be tested in this study are TDS, pH, Fe, SO4, COD, BOD, Cu, Cl, Pb, NH3, Total Coliform. The study was conducted at 3 sample points taken by purposive sampling. The average results of the calculation of the Lau Borus Waters Pollution Index method Outlet Lau Kawar Lightly Polluted Lake (scores from 1.86 to 2.19). While the results of Permenkes number 32 of 2017 the total coliform results show that this value has exceeded the average value. These results indicate that the quality status is influenced by pollutants from Iron (Fe) and Total Coliform which are above the quality standard. The relationship between the eruption activity of Mount Sinabung and the quality of Lau Borus during sampling did not cause a significant pollution impact from volcanic ash pollutants. The cause of Lau Borus pollution is from the wind direction. The percentage results from the eruption wind direction towards Lake Lau Kawar. the direction of the lake with the opposite direction is 1: 8. The eruption towards the Lau Borus Outlet, Lake Lau Kawar, is relatively small compared to the opposite direction.